2020
DOI: 10.1186/s12967-020-02637-w
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression profiles and features in NAFLD mice: a study using RNA-seq data

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is primarily characterized by the hepatic cholesterol accumulation. Circular RNA (circRNA), one of noncoding RNA, involves in many liver diseases progression. However, no recent studies on circRNA expression profiles in NAFLD have been reported previously. Methods A NAFLD mouse model was constructed by providing high-fat diet (HFD) for 32 weeks. The circRNAs expression profile in normal mice and N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
(23 reference statements)
1
18
0
Order By: Relevance
“…Therefore, clarification the cellular and molecular mechanism of NASH has become a research hotspot. Over the course of research, it was found that circRNAs might function significantly in progression of NASH, in which a novel type of circRNAs, namely mecciRNAs, have attracted much interest recently [ 14 , 17 , 63 ]. Through bioinformatic analysis and experimental verification, this study has proposed the possibility that mecciRNAs might function as ceRNAs to regulate NASH progression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clarification the cellular and molecular mechanism of NASH has become a research hotspot. Over the course of research, it was found that circRNAs might function significantly in progression of NASH, in which a novel type of circRNAs, namely mecciRNAs, have attracted much interest recently [ 14 , 17 , 63 ]. Through bioinformatic analysis and experimental verification, this study has proposed the possibility that mecciRNAs might function as ceRNAs to regulate NASH progression.…”
Section: Discussionmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) is one of the most common liver diseases in developed countries, with the fastest growing in the USA, France and the UK. A strong increase is also observed in developing countries and worldwide in general ( 36 , 37 ). In 20–30% of cases, NAFLD slowly progresses to non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis and hepatocellular carcinoma (HCC).…”
Section: Circrnas’ Involvement In Nafld Pathologymentioning
confidence: 99%
“…circRNA expression profiles are changed in MAFLD, indicating that circular RNA may participate in the development and progression of liver steatosis. 148 , 149 Knockdown of circScd1 in liver cell line AML12 promote hepatic fat content, while overexpression of circScd1 attenuated steatosis, suggesting that circScd1 mediated hepatic steatosis. 150 circRNA_0046366 increased hepatocellular FAO via inhibiting miRNA-34a function, leading to reduced hepatic steatosis.…”
Section: Epigenetics In Mafldmentioning
confidence: 99%